The Role of Micro, Small and Medium Enterprises (UMKM) in Improving Community Welfare in Sumedang Regency, West Java - Margono, Budi; Hadijaya, Isman; Haromin (PT FORMOSA CENDEKIA GLOBAL, 2024)
Community needs for decent living When fundamental requirements are satisfied—clothing, food, shelter, and health care, for example—the community can be considered prosperous and able to carry out a variety of economic activities. Welfare is also a very basic concept. MSMEs, or MSMEs, or small and medium-sized businesses, can assist with this. This literature study aims to explain the ways in which micro, small, and medium-sized firms, or MSMEs, improve their local communities. The solution to this issue is discussed using a literature study approach. The discussion's conclusions highlight how important micro, small, and medium-sized businesses are to supporting the local economy.. This little, Small and medium-sized businesses have demonstrated their ability to handle a variety of circumstances, including the financial crisis and COVID-19, to the point that their presence has been able to contribute to boosting earnings and well-being in the neighborhood